Calcium Transport Proteins in Fungi: The Phylogenetic Diversity of Their Relevance for Growth, Virulence, and Stress Resistance - Lange, Mario; Peiter, Edgar (Frontiers in Microbiology, 2020)
The key players of calcium (Ca2+) homeostasis and Ca2+ signal generation, which are Ca2+ channels, Ca2+/H+ antiporters, and Ca2+-ATPases, are present in all fungi. Their coordinated action maintains a low Ca2+ baseline, allows a fast increase in free Ca2+ concentration upon a stimulus, and terminates this Ca2+ elevation by an exponential decrease – hence forming a Ca2+ signal. In this respect, the Ca2+ signalling machinery is conserved in different fungi. However, does the similarity of the genetic inventory that shapes the Ca2+ peak imply that if "you've seen one, you've seen them all" in terms of physiological relevance? Individual studies have focused mostly on a single species, and mechanisms elucidated in few model organisms are usually extrapolated to other species. This mini-review focuses on the physiological relevance of the machinery that maintains Ca2+ homeostasis for growth, virulence, and stress responses. It reveals common and divergent functions of homologous proteins in different fungal species. In conclusion, for the physiological role of these Ca2+ transport proteins, “seen one”, in many cases, does not mean: “seen them all”.